Evolution of microbiota during spontaneous and inoculated Tonda di Cagliari table olives fermentation and impact on sensory characteristics. (October 2017) - Comunian, R.; Ferrocino, I.; Paba, A.; Daga, E.; Campus, M.; Di Salvo, R.; Cauli, E.; Piras, F.; Zurru, R.; Cocolin, L.
Abstract: Starters are widely used for driving food fermentations faster and more safely. Recently, the use of natural autochthonous microbiota is being reappraised for obtaining products with peculiar and unique characteristics. The aim of this study was to investigate, by DGGE and REP-PCR(GTG)5, the microbial dynamics and intra-species biodiversity of Tonda di Cagliari table olives inoculated with a mix of autochthonous Lactobacillus pentosus strains (SIE) or a single Lactobacillus plantarum strain (SSL), taking spontaneous fermentation (NF) as control. Furthermore, the sensory quality of the three fermentations trials was evaluated by Descriptive Analysis. Among 316 isolates, 289 were identified as Lactobacillus pentosus, and only 31, coming exclusively from batches SSL, as Lactobacillus plantarum . The predominance of L. pentosus can be explained by their better adaptation to the olive fermentation environment with respect to L. plantarum selected strain inoculated in SSL fermentations. Using the culture independent approaches, differences in the fermentation processes were shown only during the first months of fermentation, and several Gram negative species, not frequently isolated in these ecosystems ( Thalassomonas agarivorans, non-fermentative bacteria, and the cyanobacteria Chroococcidiopsis ), were identified. Autochthonous starter SIE, compared to SSL, produced olives more similar, in sensory attributes, to the naturally fermented ones. Highlights: L. pentosus confirmed to be a very competitive species in table olive fermentations. Autochthonous strains were able to overcome the L. plantarum monostrain starter. Autochthonous starter produced table olives with good and constant quality. DGGE detected Gram negative species, not frequently isolated in table olives. Autochthonous starter produced same sensory quality as natural traditional table olives in a shorter time.